2020
DOI: 10.3390/sym12121965
|View full text |Cite
|
Sign up to set email alerts
|

Moving Object Detection Based on Background Compensation and Deep Learning

Abstract: Detecting moving objects in a video sequence is an important problem in many vision-based applications. In particular, detecting moving objects when the camera is moving is a difficult problem. In this study, we propose a symmetric method for detecting moving objects in the presence of a dynamic background. First, a background compensation method is used to detect the proposed region of motion. Next, in order to accurately locate the moving objects, we propose a convolutional neural network-based method called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Recently, Deep Learning (DL) has been proposed to achieve good results in detecting moving objects in the camera environment [8]. For example, Convolution Neural Networks (CNN) models in video processing have provided impressive results in tracking moving objects [9], Recurrent Neural Networks (RNN) models can be applied to various vision Data 2022, 7, 40 2 of 7 tasks that involve sequential inputs and outputs, such as detecting the activity of an object in time [10], or using You Only Look Once YOLO, a DL-based real-time object detection algorithm [11]. The tremendous success of road traffic monitoring systems has been made possible primarily by improvements in the methodology for moving objects, the availability of appropriate datasets, and the computational gains achieved with GPU cards.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Deep Learning (DL) has been proposed to achieve good results in detecting moving objects in the camera environment [8]. For example, Convolution Neural Networks (CNN) models in video processing have provided impressive results in tracking moving objects [9], Recurrent Neural Networks (RNN) models can be applied to various vision Data 2022, 7, 40 2 of 7 tasks that involve sequential inputs and outputs, such as detecting the activity of an object in time [10], or using You Only Look Once YOLO, a DL-based real-time object detection algorithm [11]. The tremendous success of road traffic monitoring systems has been made possible primarily by improvements in the methodology for moving objects, the availability of appropriate datasets, and the computational gains achieved with GPU cards.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the initial separation of the object and background and output the bounding box of cows for pose estimation, we built a multiobject model prior to pose estimation. In recent years, much research has been conducted on multiobject detection [ 29 – 31 ]. In this study, the YOLO v4 network which is a one-stage object detection algorithm was used to carry out fast and accurate detection of multiple cows.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported a 94.1% improvement in vehicle detection accuracy. There is another study conducted by Zhu et al [22] on moving vehicles (airplane, car, and person) detection using the YOLOv3 in conjunction with background subtraction image frames in videos. They reported 91% mAP and 27 frames per second (FPS).…”
Section: Literature Reviewmentioning
confidence: 99%